Perilous Passages - Chappell, Julie. author. aut Link
XLV, 173 p.
Keywords: This study will significantly further our interpretations of the unique autobiography of Margery Kempe, lay woman turned mystic and visionary. Following the manuscript from a Carthusian monastery through history, Chappell bridges the gaps in our understanding of the transmission of texts from the medieval past to the present.